Pengaruh Kompres Dingin terhadap Nyeri Pasca Tindakan Radiofrequency Ablation (RFA) - Yanuar Widayati; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (PPNI UNIMMAN, 2026)
RFA treatments, pain is a frequent issue that might interfere with comfort and postpone recovery. Pharmacological treatment continues to be the mainstay of pain management after RFA, whereas non-pharmacological nursing treatments like cold compress therapy are not regularly used. The purpose of this research was to investigate how cold compress therapy affects pain severity in individuals following radiofrequency ablation. At the central general hospital in central Java, a quantitative quasi-experimental design was used, employing a one-group pre-test and post-test methodology. Twenty-eight participants were chosen using purposive sampling. The NRS was used to assess the intensity of pain both before and after applying a cold compress for 15–20 minutes. The Wilcoxon Signed Rank Test was used to examine the data. Following the intervention, the median pain scores fell from 5 (moderate pain) to 2 (mild pain), which was a statistically significant change (p = 0.001). These results suggest that cold compress therapy can be advised as a non-pharmacological nursing intervention in post-procedural treatment since it helps lessen post-RFA pain